Determining the standard levels of cognitive flexibility for master’s students of institute of sciences and techniques of sports physical activities Mohamed Boudiaf Msila university. - بوغرة أمينة; حملاوي عامر (My University, 2023)
The research aims to determine the standard levels of cognitive flexibility for master’s students of institute of sciences and techniques of sports physical activities Mohamed Boudiaf Msila university, we used the descriptive approach in this study, the research sample included 50 master’s students, of whom 25 from level 1 and 25 from level 2, we choose them with random method, We used the cognitive flexibility scale as instrument and the SPSS program to reach accurate results, at the end of this study the results indicated that there is a moderate level in cognitive flexibility for students of sport and there are no significant differences in cognitive flexibility and its sub-skills according to master’s level (level 1 and level 2).
Keywords: cognitive; flexibility, cognitive flexibility.